Arbuscular Mycorrhizal Fungi Associated with Wati (Piper methysticum), a Medicinal Plant from Merauke Lowland, Papua, Indonesia - Suharno Suharno; Supeni Sufaati; Verena Agustini; Rosye H. R. Tanjung (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Indonesia is rich of natural resources, including the diversity of agricultural crops and other valuable plants. Many plant species used by local people for traditional herbal medicine and some other species used by drug industries. Among these, Wati (Piper methysticum, Piperaceae) is one of the medicinal plant found in Merauke lowland, Papua. It has been cultivated by local people because of it high value as medicinal and cultural uses. Wati plant is used to treat anti-stress, rheumatism, respiratory tract infections, tuberculosis, gonorrhea, headache etc. The habitat, including the microorganism in the soil plays an important role in the growth of this plant. Therefore, this study was conducted to identify the arbuscular mycorrhizal fungi (AMF) associated with the rhizosphere of Wati from Merauke lowland. Soil and root samples were collected from different locations and the colonization percentage on the root sample were determined. Our results showed that the number of the spores in the soil samples was 45-89 spores/50 g soil, while the colonization percentage on the root was 38.46-83.3%. Among 13 AMF morphospecies that found on the soil samples, 10 were identified to genus level such as Glomus, Clariodeoglomus, Acaulospora and Scutellospora, while the other were unidentified. Further work will be needed such as trap-plant culture method to get more information on the diversity of AMF associated with Wati.